Wild - From Lost to Found on the Pacific Crest Trail - Strayed, Cheryl 1968-; Dunne, Bernadette; Musselman, Dan.; Random House Audio Publishing (New York : Random House Audio, 2012)
A powerful, blazingly honest, inspiring memoir: the story of a 1,100 mile solo hike that broke down a young woman reeling from catastrophe--and built her back up again.
Keywords: Strayed, Cheryl, -- 1968- -- Travel -- Pacific Crest Trail; Authors, American -- Biography -- 21st century; Audiobooks; Pacific Crest Trail -- Description and travel; Audiobooks